NURSING CARE FOR HYPERTENSION CONTROL IN PRIMARY HEALTH CARE: EFFECTIVENESS AND STRATEGIES - Taciano, Gleiziane dos Santos; Mendes, Millena Santini; Sousa, Denilson Welliton dos Anjos; Netto, Getúlio José do Carmo Neves; Lemos, Alda Lima; Gomes, Glauciney Pereira; Conde, Guilherme Augusto Barros; Conde, Valney Mara Gomes (Seven Editora, 2026)
Objective: To synthesize and discuss the scientific evidence on the role and effectiveness of nursing care in the control of Systemic Arterial Hypertension in Primary Health Care settings.Method: This is a narrative literature review. The search was conducted in the LILACS, SciELO, and PubMed/MEDLINE databases, encompassing publications between 2020 and 2025. Nineteen relevant studies were selected, including randomized clinical trials, systematic reviews, cohort studies, and qualitative research. The synthesis of knowledge was organized into thematic categories.Results: The most effective nursing interventions include: health education strategies (with a reduction in systolic blood pressure of up to 5.8 mmHg); blood pressure monitoring (with reductions of 3.3 to 8.5 mmHg); support for medication adherence; lifestyle modification programs; and nurse-led care models, such as nursing clinics and case management, which demonstrated reductions in systolic blood pressure between 5.4 and 12.41 mmHg. Outcomes include improved blood pressure control, increased adherence rates, enhanced disease knowledge, and improved quality of life.Conclusion: The evidence confirms that nursing care is fundamental and highly effective for the control of hypertension in primary health care. Nurse-led interventions, particularly when integrated into collaborative models, result in better clinical outcomes.